O cinema da paixão: cultura espanhola na mídia - Marques, Sílvia Cristina Aguetoni (2009)
The current research has as main objective to uncover combinations between religious / Christian European elements and eroticized / flamenco Arabian elements that started to take shape in Spain from the 8th century on and keep being reelaborated nowadays in a constant process of tense coexistence. In order to achieve this objective, some movies by relevant film directors for the subject matter (such as Luis Buñuel, Pedro Almodóvar, Carlos Saura, and Bigas Luna) will be used, establishing the hybrid and baroque Spanish culture through the movies. Despite the fact that these moviemakers belong to different provinces and times and that they have distinctive styles, the four of them exhaustively work or have worked with great icons from Spanish culture: bullfights, typical dishes, such as paella and tortilla, flamenco dance and music, terrorist attacks after Franco s era. The thesis was developed based on examples from movie scenes. Analyzed together with screenwriters and the theory of mestizaje, these examples make explicit the tense combination of different elements of Spanish culture